Assessment of free and immobilized kefir culture in simultaneous alcoholic and malolactic cider fermentations. (March 2017) - Nikolaou, Anastasios; Galanis, Alex; Kanellaki, Maria; Tassou, Chrysoula; Akrida-Demertzi, Konstantoula; Kourkoutas, Yiannis
Abstract: The aim of the present study was to assess application of free or immobilized kefir culture on apple pieces and delignified cellulosic material (DCM) in simultaneous alcoholic and malolactic cider fermentations at a wide temperature range (5–45 °C). Repeated batch fermentations were continued for higher than 7 months, showing a high operational stability of the systems and were completed in less than 24 h with immobilized cells on DCM at 37 °C. Malic acid conversion up to 71.5% and ethanol productivity values up to 56.9 g/(Ld) were recorded, which could be adopted by the industrial sector. PCR-DGGE analysis of kefir culture showed no changes in microbial diversity during cell immobilization and fermentations. Analysis of major volatiles documented a significant increase of ethyl acetate content and a decrease of higher alcohols at low temperatures. HS-SPME GC/MS analysis revealed that the highest content of esters and total volatiles was observed in cider fermented by kefir culture immobilized on apple pieces at 20 °C. Principal Component Analysis showed that mainly the immobilization support rather than the temperature had a significant effect on volatile composition. Finally, the sensory evaluation ascertained the high quality of the new products. Highlights: Kefir culture was assessed in alcoholic and malolactic cider fermentation. Free or immobilized cells were tested in repeated batch fermentations at 5–45 °C. Ethanol productivity up to 56.9 g/L d was recorded. Malic acid conversion ranged up to 71.5%. Both kefir culture and temperature had a significant effect on volatiles.